Decision Support System for Determining Character Education Values - Wahyu Putri Lestari; Puji Handayani Putri; Setia Wardani (Journal of Intelligent Software Systems, 2023)
The 2013 curriculum is an effort made by the government in improving the curriculum according to the needs of the current generation. This 2013 curriculum is a curriculum that does not only focus on academic competence, but also includes aspects of student character and skills. However, in its implementation, the 2013 curriculum makes teachers feel confused, especially in the assessment of attitudes and character. The assessment carried out with Rubik and observation sheets has indicators that are not appropriate so that character assessment becomes inappropriate. This research will design a system to conduct student character assessment at SDN Butuh 1 Magelang. In this research, a system will be designed to help teachers conduct student character assessment with SPK character assessment in Indonesia. The method applied in this research is the Simple Additive Weighting (SAW) method. The result of this research is a system to support the decision of students' character education value.